Death and non-lethal weapons: A case of homicide by penetrating injury without projectile. (August 2022) - Borges, J.; Sautier, C.; Krebs-Drouot, L.; Henry, P.; Paysant, F.; Scolan, V.
Abstract: Herein, we report the death of a man, approximately thirty years old, victim of a short-range shot to the thorax from a PIEXON JPX4, a hand weapon classed category D in France, said to be non-lethal. External examination of the lesion revealed characteristics similar to those of ballistic injuries. The autopsy found an intercostal wound that reached the pulmonary parenchyma and the pulmonary artery, with severe hemothorax. By the end of the autopsy, no projectile had been found in the body, nor any exit orifice. Death was caused by the effects of hemorrhagic shock. The PIEXON JPX4 has four cartridges, projecting a capsaicin gel that is designed to irritate the ENT area (ear nose throat) to incapacitate an assailant. The manufacturer recommends not to use it at distances of less than 1.5 m. Experimental shots were performed on gelatine blocks at point-blank range and at distances of 5, 10, 20, 30, 50, 100 and 150 cm to evaluate the distance necessary for the jet of gel to have a penetrating effect. Shots at 5–30 cm penetrated the structure. None of the other shots were penetrating. The autopsy and experiment data therefore show the penetrating potential of the jet of gel. Herein, we report the first death due to use of the PIEXON JPX4. From a forensic investigation viewpoint, we add a new exception to the "bullet rule". (The odd and even bullet rule states that if the number of gunshot wounds of entrance and exit found in the body is even, the presumption is that no bullet is lodged in the body. If the number of gunshot wounds of entrance and exit is odd, the presumption is that one or more bullets have been lodged in the body.). Highlights: We reported the case of a man, who bled to death after a chest wound inflicted by another man with the PIEXON JPX4, a weapon normally used for self-defense. At the autopsy, the chest wound was very similar to a gunshot injury. PIEXON JPX4 project a capsaicin gel which played the role of the bullet. We reported another case of lethal injury caused by a self-defense arm. Awareness about the dangers of these weapons is still necessary. The case is an exception of the rule of parity, with a chest wound alike a gunshot injury without projectile at the autopsy.